Relationship among Big Five Personality Traits, Job Performance & Job Satisfaction: A Case of School Teachers in Sri Lanka - Chandrasekara, W.S. (International Journal of Information, Business and Management, 2019)
This study aims to examine the relationships among Personality traits, Job Satisfaction and Job performance. A sample study was conducted with 150 government school teachers using a closed ended questionnaire based on Personality Traits developed by Norman and McCrae & Costa, Job Performance developed by Borman & Motowidlo’s, Task Performance developed by McAllister’s, Contextual Performance developed by Organ and Farh’s et al., and Job Satisfaction developed by Porter & Lawler, and Organ. Face to face interview method was performed and data was analyzed using SPSS 20.0. Job satisfaction and job performance show a reciprocal significant relationship. All the personality traits significantly influence on job performance whereas the Agreeableness indicates the greatest effect. In terms of job satisfaction, Agreeableness is most influential factor, followed by Extraversion. The other three personality factors do not have effect on job satisfaction. The contribution of this study is to provide empirical support for the reciprocal effect of job performance and job satisfaction. These findings confirm the previous studies’ causal relationship between these two variables.
Keywords: Big five personality traits; Job satisfaction; Job performance; Sri Lanka